Women's facial attractiveness is related to their body mass index but not their salivary cortisol. Issue 3 (26th September 2015) - Han, Chengyang; Hahn, Amanda C.; Fisher, Claire I.; Debruine, Lisa M.; Jones, Benedict C.
Abstract : Objectives: Although many theories of human facial attractiveness propose positive correlations between facial attractiveness and measures of actual health, evidence for such correlations is somewhat mixed. Here we sought to replicate a recent study reporting that women's facial attractiveness is independently related to both their adiposity and cortisol. Methods: Ninety‐six women provided saliva samples, which were analyzed for cortisol level, and their height and weight, which were used to calculate their body mass index (BMI). A digital face image of each woman was also taken under standardized photographic conditions and rated for attractiveness. Results: There was a significant negative correlation between women's facial attractiveness and BMI. By contrast, salivary cortisol and facial attractiveness were not significantly correlated. Conclusions: Our results suggest that the types of health information reflected in women's faces include qualities that are indexed by BMI but do not necessarily include qualities that are indexed by cortisol. Am. J. Hum. Biol. 28:352–355, 2016. © 2015 Wiley Periodicals, Inc.